Omni-Gesture: A Hand Gesture Interface for Omnidirectional Devices - Kim, Heesun; Lee, Dongeon; Park, Ji-Hyung; Jang, Hyejin; Kim, Min Gyeong (COMPANION OF THE 23RD INTERNATIONAL CONFERENCE ON INTELLIGENT USER INTERFACES (IUI'18), 2018)
We present "Omni-Gesture", a new omnidirectional hand gesture interface for smart interactive devices. Unlike voice user interface, this interface recognizes the direction of a user's gesture and provides visual feedback accordingly. We developed an experimental prototype system with Omni-Gesture in order to explore it in usability. The system has a cylindrical screen, implementing an interactive aquarium application. Omni-Gesture provides more accurate feedbacks for users in three stages. First, the system recognizes the gesture by analyzing camera images. Second, it integrates the recognized data into direction information. Last, it identifies the user's control between "Access" and "Shift", and then it provides feedback toward the direction. Through the preliminary study, we found that using Omni-Gesture for omnidirectional devices is promising if the recognition speed can be improved, especially when moving. We also discuss future work for developing various gesture sets to use alongside other interfaces and applying OmniGesture to other omnidirectional platforms.